Beyond the Deal: Using Industrial Recruitment as a Strategic Tool for Manufacturing Development. (November 2014) - Lowe, Nichola J.
Industrial recruitment continues to play a significant role in the development of manufacturing industries in the U.S. South. Still, there are signs of shifting practice that not only emphasize a different set of regional advantages from earlier decades but equally help bolster those same advantages to anchor outside firms to the region. This article presents a case study of the strategic use of industrial recruitment to build out North Carolina's biopharmaceutical manufacturing industry. This case study helps shed light on how recruitment practices can be designed and improved to support continued manufacturing job growth, but in ways that also limit the recruitment of potentially footloose establishments. As such, it presents an alternative perspective to recent studies of industrial recruitment that focus narrowly on efforts to limit or curb locational incentives for industry attraction.